Non-Conventional Clinical Uses of TSH Receptor Antibodies: The Case of Chronic Autoimmune Thyroiditis - Napolitano, Giorgio; Bucci, Ines; Di Dalmazi, Giulia; Giuliani, Cesidio (Frontiers in Endocrinology, 2021)
Anti TSH receptor antibodies (TSHrAb) are a family of antibodies with different activity, some of them stimulating thyroid function (TSAb), others with blocking properties (TBAb), it is a common finding that antibodies with different function might coexist in the same patient and can modulate the function of the thyroid. However, most of the labs routinely detect all antibodies binding to the TSH receptor (TRAb) without distinction of the functional properties. Prevalence of TSHrAb is different in in the 2 main form of chronic autoimmune thyroiditis (CAT), i.e. classical Hashimoto’s thyroiditis and in atrophic thyroiditis, where TBAb play a major role. Simultaneous presence of both TSAb and TBAb in the serum of the same patient might have clinical implication and cause the shift from hyperthyroidism to hypothyroidism and vice versa. Evaluation of TRAb is mandatory in case of patients with Thyroid Associated Orbitopathy not associated with hyperthyroidism. At present, however, the most relevant recommendation for the use of TRAb assay is in patients with CAT secondary to a known agent; in particular, after treatment with alemtuzumab for multiple sclerosis. In conclusion, the routine use of anti-TSH receptor antibodies (either TRAb or TSAb/TBAb) assay cannot be suggested at the present for diagnosis/follow up of patients affected by CAT; there are, however, several conditions where their detection can be clinically relevant.